2013
DOI: 10.1128/aem.03980-12
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Genetic Characterization of the Enterococcus faecalis Oxaloacetate Decarboxylase Complex

Abstract: c Enterococcus faecalis encodes a biotin-dependent oxaloacetate decarboxylase (OAD), which is constituted by four subunits: E. faecalis carboxyltransferase subunit OadA (termed Ef-A), membrane pump Ef-B, biotin acceptor protein Ef-D, and the novel subunit Ef-H. Our results show that in E. faecalis, subunits Ef-A, Ef-D, and Ef-H form a cytoplasmic soluble complex (termed Ef-AHD) which is also associated with the membrane. In order to characterize the role of the novel Ef-H subunit, coexpression of oad genes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Deviating apparent molecular weight is also seen in other studies. [ 32 33 34 ] Structural rigidity and kinks caused by high proline content may decrease electrophoretic mobility of the protein. Gel shifting due to high content of proline residue in protein structure has been shown in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Deviating apparent molecular weight is also seen in other studies. [ 32 33 34 ] Structural rigidity and kinks caused by high proline content may decrease electrophoretic mobility of the protein. Gel shifting due to high content of proline residue in protein structure has been shown in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several energy-transducing steps may be discriminated in the pathway, including uptake of the Ca 2ϩ -citrate complex, which has been shown to be coupled to the uptake of protons in the case of homologous transporters (3,19,39), excretion of Ca 2ϩ by an unknown transporter that is likely to couple the flux to an antiport with protons, and the decarboxylation of oxaloacetate by the membrane-bound OAD that in the Gram-negative counterparts functions as a Na ϩ pump (6). A very recent study of the OAD complex of the closely related Grampositive bacterium Enterococcus faecalis showed that the soluble OAD-A subunit that presumably couples the decarboxylation reaction to ion pumping by the membrane-bound OAD-B subunit was found for a significant part in the cytoplasm, which potentially could have a negative effect on the free-energy conservation of the reaction (44). At any rate, the net result of the charge and proton movements across the membrane is zero, and the pathway does not seem to contribute to the metabolic energy pool in Lb.…”
Section: Discussionmentioning
confidence: 99%
“…The cit cluster is encoded in two divergent operons: citHO encoding for the citrate transporter citH , and the regulatory protein citO . The catabolic enzymes are encoded upstream, in the minus strand, in the oadHDB-citCDEFX-oadA-citMG operon (Blancato et al, 2006 , 2008 ; Espariz et al, 2011 ; Repizo et al, 2013 ). There are two binding elements for CitO in the intergenic region, which regulate the expression of genes involved in the transport and degradation of citrate.…”
Section: Introductionmentioning
confidence: 99%